2018
DOI: 10.3390/ijms19103237
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Reveals Novel Genomic Regions Associated with 10 Grain Minerals in Synthetic Hexaploid Wheat

Abstract: Synthetic hexaploid wheat (SHW; Triticum durum L. × Aegilops tauschii Coss.) is a means of introducing novel genes/genomic regions into bread wheat (T. aestivum L.) and a potential genetic resource for improving grain mineral concentrations. We quantified 10 grain minerals (Ca, Cd, Cu, Co, Fe, Li, Mg, Mn, Ni, and Zn) using an inductively coupled mass spectrometer in 123 SHWs for a genome-wide association study (GWAS). A GWAS with 35,648 single nucleotide polymorphism (SNP) markers identified 92 marker-trait as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
77
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 49 publications
14
77
0
Order By: Relevance
“…We analyzed 16 agronomic-, 16 grain mineral-, and 13 wheat rust-related phenotypes in the current study. Agronomic traits including grain yield (GY), harvest index (HI), biomass weight (BMWT), grain volume weight (GVWT), flag leaf length (FLL), flag leaf width (FLW), flag leaf area (FLA), rachis break (RB), sterile spikelet (SP), spike length (SL), seeds per spike (SPS), spikelet number (SN), fertile spikelet (FS), spike weight (SW), grain weight per spike (GPS), and spike harvest index (SHI) were measured using previously described standard procedures (Bhatta et al, 2018a;Morgounov et al, 2018;Hussain et al, 2017). Grain minerals including arsenic (As), calcium (Ca), cadmium (Cd), cobalt (Co), copper (Cu), iron (Fe), potassium (K), lithium (Li), magnesium (Mg), manganese (Mn), molybdenum (Mo), nickel (Ni), phosphorous (P), sulfur (S), titanium (Ti), and zinc (Zn) were measured via inductively-coupled plasma mass spectrometry (ICP-MS, Agilent 7500cx, Agilent Technologies, Santa Clara, CA, USA) at the University of Nebraska Redox Biology Center, Proteomics and Metabolomics Core (Guttieri et al, 2015;Bhatta et al, 2018a).…”
Section: Phenotypic and Genotypic Datamentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed 16 agronomic-, 16 grain mineral-, and 13 wheat rust-related phenotypes in the current study. Agronomic traits including grain yield (GY), harvest index (HI), biomass weight (BMWT), grain volume weight (GVWT), flag leaf length (FLL), flag leaf width (FLW), flag leaf area (FLA), rachis break (RB), sterile spikelet (SP), spike length (SL), seeds per spike (SPS), spikelet number (SN), fertile spikelet (FS), spike weight (SW), grain weight per spike (GPS), and spike harvest index (SHI) were measured using previously described standard procedures (Bhatta et al, 2018a;Morgounov et al, 2018;Hussain et al, 2017). Grain minerals including arsenic (As), calcium (Ca), cadmium (Cd), cobalt (Co), copper (Cu), iron (Fe), potassium (K), lithium (Li), magnesium (Mg), manganese (Mn), molybdenum (Mo), nickel (Ni), phosphorous (P), sulfur (S), titanium (Ti), and zinc (Zn) were measured via inductively-coupled plasma mass spectrometry (ICP-MS, Agilent 7500cx, Agilent Technologies, Santa Clara, CA, USA) at the University of Nebraska Redox Biology Center, Proteomics and Metabolomics Core (Guttieri et al, 2015;Bhatta et al, 2018a).…”
Section: Phenotypic and Genotypic Datamentioning
confidence: 99%
“…Previous studies revealed the negative genetic associations of yellow and stem rust traits with grain yield traits. Wheat rust diseases are foliar fungal diseases whose infection on the flag leaf close to the grain filling period causes a decline in the photosynthetic ability of the plant, drastically decreasing the grain filling process and reducing the biomass yield, thousand kernel weight, and harvest index (He et al, 2019;Bhatta et al, 2018a;Herrera-Foessel et al, 2006). Thus, the reduction of these important traits results in a reduction in the final grain yield (SRDH → GYL and YRD → GYL).…”
Section: Biological Meaning Of the Inferred Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetics were phenotyped in Turkey under moisture stress in 2016 and 2017 and variable disease infections and genotyped by sequencing in USA. A number of genes were identified for grain yield and its components under drought [32] , common bunt resistance [33] and minerals content [34] . Several synthetic wheat lines were tested in Azerbaijan and also demonstrated superior yield performance and tolerance to salinity [35] .…”
Section: Impactmentioning
confidence: 99%
“…Nevertheless, the developments in sequencing methodologies, decreased sequencing price, together with the advancements in the computational resources have permitted the spread of these resources [39,40]. Besides, the comparative genomics among plant species is demonstrating to be an efficient method for the identification of novel genes regarding the biofortification of modern wheat [41]. Therefore, in this review, we have compiled the QTLs Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted:…”
mentioning
confidence: 99%